THE IMPORTANCE OF INTERCULTURAL COMMUNICATION IN FOREIGN LANGUAGE LEARNING: THE IMPORTANCE OF INTERCULTURAL COMMUNICATION IN FOREIGN LANGUAGE LEARNING - Anefiyaeva, Anzhela (Журнал иностранных языков и лингвистики, 2025)
The purpose of the article is to form students' professional communicative competencies with effectiveness in the process of the foreign language professional communication in standard-known and unknown-standard situations of the interpersonal, business and professional aspects with foreign citizens in the performance of professional duties and responsibilities. For achieving the result, the learning process is aimed at improving the professional competence in the field of the professional documentation, colloquial clichés and vocabulary in a foreign language, which have become widespread in all life`s spheres, given widely in the worldview of foreign languages in cultural and professional connections, in the field of the professional development, research and teaching. The impacts and challenges of these transformations require careful learning. The students of the institute or university prospect for future work, express motivation in mastering a foreign language as part of their career priorities in a professional environment. The main tendencies due to intercultural communication are aimed among students as they must perceive the real globalization of the world and understand a foreign language environment. The development of a foreign language as an international tool communication is reaching the level of using such language as a popular one. It has been repeatedly emphasized and substantiated by scientists and linguists and others.